SUMBER GANGGUAN KEJIWAAN TOKOH UTAMA DALAM NOVEL ROMANSA 2 BENUA KARYA PIPIET SENJA PERSPEKTIF PSIKOLOGI HUMANISTIK ABRAHAM MASLOW - Indarwati Indarwati; Nensilianti Nensilianti; Mahmudah Mahfud (Fakultas Bahasa dan Sastra Indoensia, 2024)
The research design used is descriptive. This type of research is qualitative. The research data is the text of the novel Romansa 2 Benua by Pipiet Senja, page number 223, published in 2015. The techniques used are documentation, reading, and note-taking techniques. The findings from the results of this study are frustration, conflict, and threats. And the way to recover is to use a humanistic psychological approach with a motivational approach.